Callus Induction, Proliferation, and Plantlets Regeneration of Two Bread Wheat (Triticum aestivum L.) Genotypes under Saline and Heat Stress Conditions. (15th December 2011) - Benderradji Benderradji, Laid Laid; Brini Brini, Faiçal Faiçal; Kellou Kellou, Kamel Kamel; Ykhlef Ykhlef, Nadia Nadia; Djekoun Djekoun, Abdelhamid Abdelhamid; Masmoudi Masmoudi, Khaled Khaled; Bouzerzour Bouzerzour, Hamenna Hamenna
Abstract : Response of two genotypes of bread wheat ( Triticum aestivum ), Mahon-Demias (MD) and Hidhab (HD1220), to mature embryo culture, callus production, and in vitro salt and heat tolerance was evaluated. For assessment of genotypes to salt and heat tolerance, growing morphogenic calli were exposed to different concentrations of NaCl (0, 5, 10, and 15 g·L −1 ) and under different thermal stress intensities (25, 30, 35, and 40°C). Comparison of the two genotypes was reported for callus induction efficiency from mature embryo. While, for salt and heat tolerance, the proliferation efficiency, embryonic efficiency, and regeneration efficiency were used. The results show significant medium and genotype effects for the embryogenesis capacity of calluses induction and plantlets regeneration under saline and thermal stresses. Mahon-Demias showed good callus induction and ability to proliferate and regenerate seedling under heat and salt stress conditions compared to Hidhab. No sizeable differences were observed between the two genotypes at higher salt stress rates. This study will serve as a base line for in vitro screening of several elite wheat cultivars for their ability to induce callus and regenerate plants from mature embryos, and to start selection for tolerance to salinity.